Embryonic development and larva of the toad Incilius aucoinae (Bufonidae) in Golfito, Costa Rica. - Segura-Solís, Susy (2009)
The larva and developmental stages of Incilius aucoinae are described using specimens from Río Cañaza, Golfito, Costa Rica. We collected the individuals in January 1997, and January and February 1998. The total sample was 696 individuals, 317 eggs in 1-12 stages, 176 eggs with embryos in stages 15-16, and 204 tadpoles in stages 21-43. The average number of eggs per nest was 8 940 (n = 4). These eggs were laid in strings, attached to the river strata. Eggs in stages 1-12 had an average diameter of 1.75 (s = 0.38) mm and eggs with embryos in stages 15 -16 measured 1.33 (0.34) mm wide and 3.06 (1.46) mm long. The description of the tadpole based on UCR 19982 is as follows: dorsal, ventral surfaces, and tail are brown with dark brown spots. Length of tail 9.43 mm, body length 6.18 mm (total length 15.62). Translucent light brown small fins, dorsal fin with scattered spots, ventral fin without dark pigments. Dorsal-ventral flattened oval body with anteroventral snout. A few individuals had varied colors, from black (3.4%) to uniform (0.5-1.5%).